Manajemen Kegiatan Dana Alokasi Khusus Fisik di Dinas Pendidikan Provinsi Jawa Barat - Sulaeman; Syafiatun Nabila; Rendi Harmawan; Siti Nur Ni’mah; Ahmad Farihin; Ilham Agustian Widia Yusuf (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2023)
This article discusses the management of special physical allocations at the West Java Education Office to find out how the organization's progress in the Social Council is. The method used in this study uses qualitative methods through a descriptive approach, the data sources used in this study use primary and secondary data sources, the type of data used in this study is a qualitative approach, the data collection technique used in this study is observation. and documentation. This article explains that the Special Fund is an allocation of APBN revenues that is earmarked for certain regions and is intended to finance certain activities that are regional in nature and in accordance with national priorities. From the statement above it is clear that the management of extra-budgetary funds is the management of funds for school needs, such as the construction and renovation of new classrooms, offices and toilets.